THE EFFECT OF PERCEPTIONS OF ORGANIZATIONAL SUPPORT ON DECISION MAKING DURING THE COVID-19 PANDEMIC - Eka Saputri, Darisma; Setiawan Wicaksono, Awang; Fitri Sholichah, Ima (Journal Universitas Muhammadiyah Gresik Engineering, Social Science, and Health International Conference (UMGESHIC), 2021)
This study aims to determine whether the perception of organizational support has an effect on decision making during the Covid-19 pandemic. This study uses a quantitative approach. The sample technique used is the saturated sample technique. The method of collecting data from the two variables used a questionnaire arranged in the form of a Likert scale. Analysis of research data using simple non-linear regression techniques. The results showed that for the R (square) value of 0.234 or 23.4% of the perception of organizational support to influence decision making. Meanwhile, 76.6% is influenced by other factors which are not examined. Based on data analysis, it can be concluded that there is an effect of perceived organizational support on organizational support on decision making during the Covid-19 pandemic.